Performance evaluation and damage assessment of steel frame buildings under main shock aftershock earthquake sequences. - Li, Quanwang
Structures subjected to earthquake ground motions may be subjected to one or more aftershocks within a short period following the occurrence of the principal earthquake shock. Strong aftershocks have the potential to cause extensive structural damage, property losses and injuries to building occupants. This paper investigates the potential for aftershocks to cause additional damage to steel moment frame buildings, and provides a probabilistic description of structural damage states prior to and following those aftershocks. Statistics of structural response and damage states for steel frame buildings subjected to main shock?aftershock sequences are calculated using the enhanced uncoupled modal response history analysis (EUMRHA) method, a modification of an efficient and accurate method for predicting nonlinear response of frames. The frame connections are modelled by a moment?rotation relationship that takes brittle fracture of the connection welds into account. Damage accumulation is analysed in terms of a normalized ?damage ratio? and maximum inter-storey drift. Simple probabilistic tools are proposed for purposes of rapid structural evaluation and condition assessment of damaged buildings.
Keywords: Buildings; Connections; Damage; Earthquake engineering; Probability; Reliability; Steel; Structural engineering